Morphology and Phylogeny Reveal A New Species Of Papiliomyces (Clavicipiteae, Hypocreales) From Yunnan, China - Chen, Yue; Sun, Tao; Tang, De-Xiang; Liu, Zuo-Heng; Ma, Jin-Mei; Yu, Hong (Phytotaxa, 2024)
A new species of Papiliomyces, named as Papiliomyces albostromaticus, was discovered from Deze Village, Zhanyi District, Qujing City, Yunnan Province, China. It was characterized by producing clavate, white stromata, cylindrical, black to greyish white fertile part, completely immersed, long ovoid or teardrop perithecia, cylindrical asci, cylindrical conidiophores, ampoule shaped phialides, ellipse or oval conidia. Based on the combined dataset of ITS, nrSSU, nrLSU, tef-1α, rpb1 and rpb2, multigene phylogenetic analysis showed that the specimens of this species formed a distinct clade with satisfactory bootstrap support, indicating the presence of a novel species of the genus Papiliomyces. The new species was described and illustrated in the present study. The phylogenetic tree would provide a basis for a phylogenetic study of Papiliomyces and its related genera.